You drive a total distance of 49.4 kilometers when you travel 27.54 kilometers to school and then 21.86 kilometers to your friend's house.
When you drive 27.54 km to school and then 21.86 km to your friend's place, you are covering a total distance of 49.4 kilometers. To calculate this, you simply add the two distances together:
Distance to school: 27.54 km
Distance to friend's place: 21.86 km
Total distance = 27.54 km + 21.86 km = 49.4 km
So, you drive a total of 49.4 kilometers when you travel to both school and your friend's house. This cumulative distance is the sum of the individual distances you cover for each leg of your journey. It's important to keep track of such distances, especially if you want to estimate fuel consumption, plan your commute, or calculate travel time accurately. In this case, you've covered 49.4 kilometers in total, which is the combined distance for your trip.
for more such questions on distance
#SPJ3
Answer:
49.4 km
Step-by-step explanation:
you add 27.54 plus 21.86 so 49.4 km total between school and to your friends house
h(x)=-49x-125
The transformations of f(x) = - 2lx - 3| + 1 from the parent function f(x) =|x|
Horizontal Shift: Right 3 Units
Vertical Shift: Up 1 Units
Reflection about the x-axis: Reflected
Vertical Stretch: Stretched
What is Transformation equation ?
Transformation of an equation into another equation whose roots are. reciprocals of the roots of a given equation we replace x→x1. 2.
Given,
Parent function f(x) = |x|
f(x) = - 2 lx - 3| + 1
Assume that f(x) = |x| is y = |x| and,
f(x) = - 2 lx - 3| + 1 is g(x) = - 2 lx - 3| + 1
The transformation from the first equation to the second one can be found by finding a, h, and k
y = a |x−h| + k
find a, h, k in f(x) = - 2lx - 3| + 1
a = -2, h = -3, k = 1
Horizontal shift depends on the value of h,
g(x) = f(x + h) ---- The graph is shifted to the left h units.
g(x) = f(x - h) ---- The graph is shifted to the right h units.
so, h = -3 then horizontal shift will be right 3 units
The vertical shift depends on the value of k,
g(x) = f(x) + k ------- The graph is shifted up k units.
g(x) = f(x) - k -------- The graph is shifted down k units.
so, k = 1 then the vertical shift will be 1 unit up
The sign of a describes the reflection across the x-axis,
−a means the graph is reflected across the x-axis.
Reflection about x-axis is reflected
The value of a describes the vertical stretch or compression of the graph
a > 1, vertical stretch will be narrower
a < 1, vertical stretch will be wider
so, vertical stretch is Stretched
Hence, The transformations of f(x) = - 2lx - 3| + 1 from the parent function f(x) =|x|
HorizontalShift: Right 3 Units
Vertical Shift: Up 1 Units
Reflection about the x-axis: Reflected
Vertical Stretch: Stretched
The graph is given below ↓
To read more about the Transformation equation.
#SPJ13
f(x) = 3x + 45
f(x) = −3x + 60
f(x) = 3x + 60
Answer:
f(x) = -3x+60
Step-by-step explanation:
For the slope of the function:
For the intercept of the function:
Therefore:
f(x) = -3x+60
Answer:
c
Step-by-step explanation:
b. 7
c. 8
c. 9
Box-and whisker plot titled Temperatures in Celsius ranging from 12 to 48 with the five number summary from left to right 18, 25, 28, 33, and 42
Answer:20 cm
Step-by-step explanation:
Volume of cone=540π
Radius=r=9
Volume of cone=1/3 x π x r^2 x h
540π=1/3 x π x 9^2 x h
540π=1/3 x π x 9 x 9 x h
540π=(1xπx9x9xh)/3
540π=(81πh)/3
540π=27πh
Divide both sides by 27π
540π/27π=(27πh)/27π
20=h
h=20
Height =20 cm
Answers:
The first blank is 180
The second blank is 60
======================================
The triangle sum theorem basically says that adding up all three angles of any triangle always leads to 180 degrees. So that's why
(angle1)+(angle2)+(angle3) = 180
x+x+x = 180
3x = 180
Divide both sides of that last equation by 3. This is to undo the multiplication of 3 done to x.
3x = 180
3x/3 = 180/3 ... divide both sides by 3
x = 60
Each angle of this equilateral triangle is 60 degrees. In an equilateral triangle, all three sides are the same length. Also in an equilateral triangle, all three angles are the same measure and always 60 degrees.
The Triangle Sum Theorem says that all angles in a triangle add up to 180 degrees. In an equilateral triangle, all angles are equal. Hence, each angle is 60 degrees.
The Triangle Sum Theorem states that the sum of the measures of the angles in a triangle is always 180 degrees. Now, in an equilateral triangle, all angles are equal. Let's denote the measure of each angle with x. According to the theorem, the sum of these measures is x + x + x = 180. Simplifying this gives 3x = 180. Hence, solving for x, which refers to the measure of each angle in the equilateral triangle, we get x = 180 / 3 = 60 degrees. Thus, each angle in an equilateral triangle measures 60 degrees.
#SPJ2